2015
DOI: 10.1007/s40264-014-0250-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety Surveillance of Traditional Chinese Medicine: Current and Future

Abstract: Herbal medicine, including traditional Chinese medicine, has been used for the prevention, treatment, and cure of disorders or diseases for centuries. In addition to being used directly as therapeutic agents, medicinal plants are also important sources for pharmacological drug research and development. With the increasing consumption of herbal products intended to promote better health, it is extremely important to assure the safety and quality of herbal preparations. However, under current regulation surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
154
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(155 citation statements)
references
References 74 publications
0
154
0
1
Order By: Relevance
“…Similar problems are evident for most herbs used in the context of TCM [8,12,15,17,62,63,64,65,66,67,119,120,121,122,123,124,181,185,229,230,231,232,233], which were discussed by the Chinese FDA, presenting details of the current status and future perspectives of the pharmacovigilance practice and risk control of TCM drugs in China [12]. …”
Section: Diagnostic Challengesmentioning
confidence: 59%
See 2 more Smart Citations
“…Similar problems are evident for most herbs used in the context of TCM [8,12,15,17,62,63,64,65,66,67,119,120,121,122,123,124,181,185,229,230,231,232,233], which were discussed by the Chinese FDA, presenting details of the current status and future perspectives of the pharmacovigilance practice and risk control of TCM drugs in China [12]. …”
Section: Diagnostic Challengesmentioning
confidence: 59%
“…A variety of reports and analyses focused on important issues related to the use of herbal TCM [8,9,10,41,42,43,44,45,46,47,48,49,50,51,52,53]. In particular, its integration into modern Western medicine will not easily be accomplished due to differences in philosophy and approaches of diagnoses and therapy.…”
Section: Herbal Traditional Chinese Medicine Its History Philosomentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO reported that the annual sales of herbal medicine in Germany for the year 2002 have reached US$2.432 billion [14]. Nahin et al [15] also reported that the market of HMPs in USA has expanded tremendously from US$2.9 billion to US$4.8 billion from 1995 to 2008.…”
Section: Introductionmentioning
confidence: 99%
“…After a period of 3 years, the sales of herbal medicine in China increased tremendously as reported by National Bureau of Statistics [14]. They reported that the sale value in herbal industries has reached US$68 billion (RMB418 billion) with an annual growth rate of 37.9%.…”
Section: Introductionmentioning
confidence: 99%